Evaluation of Land Suitability and Potential Development of Cardamom (Amomum compactum L.) in Padang Jaya Subdistrict, North Bengkulu Regency - Faisal, Muhammad; Sulistyo, Bambang; Hindarto, Kanang Setyo; Lovita, Vinni (BPFP Universitas Bengkulu, 2025)
Cardamom (Amomum compactum) is a high-value spice with significant applications in the pharmaceutical, food, and cosmetics industries. The increasing global demand makes cardamom a promising commodity for agricultural expan sion. However, limited information on land suitability in Padang Jaya Subdistrict poses a challenge to optimizing cultivation. This study aimed to map the land suitability classes for cardamom cultivation and assess the potential for cardamom development in Padang Jaya Subdistrict, North Bengkulu. The research involved in field surveys, soil sampling, laboratory analysis, and GIS-based land suitability evaluation using the FAO framework. Key parameters as sessed included rooting media, nutrient retention, slope, and climate condition in the past 10 years. The FAO classification system categorized land into four suitability classes, namely: S1 (high suitable), S2 (moderately suitable), S3 (marginally suitable), and N (not suitable). The result indicate the actual land suitability is predominantly S3nrnaeh and S2nrnaeh, with major limiting factors including rooting media, nutrient retention, nutrient availability, and slope. Land improvement efforts such as liming, organic matter applications, fertilization, and soil conservation techniques led to an increase in land suitability, with 62.3% of S3 land upgraded to S2 and 37.7% of S2 land reached S1. Furthermore, GIS-based analysis identified four land cover types suitable for extensification: mixed gardens, seasonal crops, plantations, and bare land, totaling 8,747.71 hectares. These findings provide valuable insights for optimizing land use planning, improving productivity, and promoting sustainable agricultural development. Integrating GIS and remote sensing in future studies could enhance land suitability assessments with a more refined spatial scale. The results also serve as a scientific reference for policymakers and farmers in designing sustainable land management strategies and minimizing environmental degradation.